Risk factors for vertebral compression fractures in preoperative chemoradiotherapy with gemcitabine for pancreatic cancer. Issue 3 (March 2016) - Otani, Keisuke; Teshima, Teruki; Ito, Yuri; Kawaguchi, Yoshifumi; Konishi, Koji; Takahashi, Hidenori; Ohigashi, Hiroaki; Oshima, Kazuya; Araki, Nobuhito; Nishiyama, Kinji; Ishikawa, Osamu
Abstract: Background and purpose: Preoperative chemoradiotherapy (CRT) with gemcitabine (GEM) for pancreatic cancer is often accompanied by vertebral compression fractures (VCFs). This study aimed to establish the incidence of VCFs and identify the related risk factors (RFs) to elucidate how to decrease the overall incidence of VCF. Material and methods: We investigated 220 patients with resectable or borderline-resectable pancreatic cancers who had completed preoperative CRT between 2006 and 2011. The RFs associated with VCF were analyzed in a total of 1308 thoracolumbar vertebral bodies. Results: Thirty-seven VCFs occurred in 25 patients (11%); the cumulative incidence at two years was 18.9%. Univariate analysis revealed female sex, age and high daily GEM concentration during radiotherapy as RFs for VCF. The multivariate mixed effects logistic regression model demonstrated that the most responsible factor was radiation dose ( p < 0.001). We estimated the radiation condition resulting in a fracture incidence of ⩽5% by counting the patient's number of the three RFs. For patients with three factors, the mean vertebral dose was 22.0 Gy. Conclusions: The RFs for VCF after CRT were identified. The side effect of VCF might be avoided by regulating the radiation dose to neighboring vertebral bodies after considering the RFs.